Simultaneous liver kidney transplantation. (21st February 2019) - Singal, Ashwani K.; Ong, Song; Satapathy, Sanjaya K.; Kamath, Patrick S.; Wiesner, Russel H.
Summary: Kidney injury is frequently seen in patients with end‐stage liver disease from cirrhosis and liver failure. Among selected patients, simultaneous liver kidney (SLK) transplantation provides improved post‐transplant graft and patient outcomes compared to liver transplantation (LT) alone. We conducted the review of the existing literature on SLK transplant criteria and outcomes. Since the introduction of the model for end‐stage disease (MELD) score in 2002, there has been an increased use of SLK transplantation. The criteria for SLK allocation are relatively homogeneous among patients with end‐stage renal disease with cirrhosis and among patients with cirrhosis and chronic kidney disease. However, these are quite heterogeneous among patients with cirrhosis and acute kidney injury (AKI), mainly because of inability to accurately differentiate cause of AKI, especially hepatorenal syndrome versus intrarenal aetiology. Clearly, there is an unmet need of urine biomarkers of tubular injury and/or clinical models to accurately stratify AKI aetiology and to predict renal recovery after LT as basis to best utilize the scarce donor kidney pool. In this regard, it remains to be seen whether recently implemented policies by the organ procurement transplant network can fulfil the goal of saving donor kidneys and optimal allocation of SLK.